(untitled) (Fiep Bulletin - online, 2024)
Study that seeks to answer the following question: - How can Games be tools for the development of students with motor learning deficits? The general objective is to observe, during Supervised Internship II classes, how Games can serve as tools for the development of students with motor deficits. Qualitative analysis carried out with 20 students, aged between 8-9 years old, using the Psychomotor Battery – BPM (Fonseca, 1995). Only one of the seven factors was selected, and the balance chosen was static, in tests 1, 2 and 3. The students presented a motor profile in the transitional stage, a specialized motor phase, as they were able to execute the movement within the age group and the test pattern; difficulty in stabilization, in single-leg balance, characterizing the fundamental motor phase, justifying the group’s difficulty in activities that require such skill. The activities were organized and adapted into a flexible lesson plan proposed for one class, with one of the contents scheduled for the academic two-month period. For Play and Games in the regional context, we selected rule games, according to Piaget (1975), to develop a better approach aimed at each age group. In the playful segment, we developed a lesson plan based on games adapted for conditions of single-leg balance in games of Job’s Slaves and English Chocolate. The research was developed as close as possible to the reality experienced by teachers, proposing a configuration to fill gaps relating to motor deficits.